(untitled) (Journal of Forensic Medicine & Toxicology, 2024)
Manual strangulation cases pose a unique challenge in forensic medicine due to the subtle nature of injuries, particularly concealed bruises that may go unnoticed during initial examinations. This case report aims to shed light on the often-overlooked signs of manual strangulation and the importance of meticulous forensic examination. We present a case involving a victim of manual strangulation where initial external examinations failed to reveal apparent signs of trauma. However, a detailed forensic analysis uncovered concealed bruises in unexpected locations, highlighting the elusive nature of injuries associated with manual strangulation. The victim’s delayed presentation further underscored the need for heightened clinical awareness and a multidisciplinary approach in such cases. Detailed documentation of the concealed bruises involved close collaboration between forensic experts, medical professionals, and law enforcement. Advanced imaging techniques, such as ultraviolet and infrared photography, played a crucial role in unmasking the hidden injuries. The case report discusses the challenges encountered during the investigation and emphasizes the importance of incorporating these innovative methods in forensic protocols. This case report underscores the significance of recognizing concealed bruises in manual strangulation cases, emphasizing the need for a comprehensive approach to forensic examinations. By raising awareness of the subtle signs associated with manual strangulation, this report aims to contribute to improved forensic practices and increased collaboration among experts in unraveling the silent but critical evidence that may be hidden beneath the surface.